How to See a Magpie: Review of Joan B. Landes, Paula Young Lee, and Paul Youngquist, eds., Gorgeous Beasts: Animal Bodies in Historical Perspective - Poliquin, Rachel (Humanimalia, 2013)
Joan B. Landes, Paula Young Lee, and Paul Youngquist, ed. Gorgeous Beasts: Animal Bodies in Historical Perspective. College Station: Penn State University Press, 2012. 258 pp. $49.95 (hb).